Analisis Potensi Risiko Usaha Sayuran pada Pekarangan Pangan LestarI (P2L) Ngongak Tanduran, Kota Madiun - Dian Ardifah Iswari; Irfan Miftahul Fauzi; Ihwan Susila; Santosa Pradana Putra Setya Negara; Sherly Oktaviana Putri; Febricha Sang Dwi Anggha (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2024)
Indonesia is a country that depends on the agricultural sector. During the Covid 19 pandemic when all sectors experienced a decline, the agricultural sector continued to record positive growth. Therefore, the Madiun City Food Security and Agriculture Service, in order to restore the economy, initiated the Sustainable Food Yard program in the form of using yards to grow vegetables which can be sold to increase household income. In 2023, funding from DKPP will stop so that P2L begins to face risk uncertainty. Risk is an uncertain situation that can hinder the achievement of goals. Therefore, risks need to be identified so that they can be handled so as not to cause major losses. The method used to identify risks is the fishbone diagram. The results of this research are that there are thirty risks that occur in the vegetable business at P2L Ngongak Tanduran. This risk is divided into five variables, namely six risks in the money variable, eight risks in the material variable, six risks in the man/personnel variable, five risks in the methods variable, and five risks in the machines variable.